The interplay between the airway epithelium and tissue macrophages during the SARS-CoV-2 infection - Barreto-Duran, Emilia; Szczepański, Artur; Gałuszka-Bulaga, Adrianna; Surmiak, Marcin; Siedlar, Maciej; Sanak, Marek; Rajfur, Zenon; Milewska, Aleksandra; Lenart, Marzena; Pyrć, Krzysztof (Frontiers in Immunology, 2022)
The first line of antiviral immune response in the lungs is secured by the innate immunity. Several cell types take part in this process, but airway macrophages (AMs) are among the most relevant ones. The AMs can phagocyte infected cells and activate the immune response through antigen presentation and cytokine release. However, the precise role of macrophages in the course of SARS-CoV-2 infection is still largely unknown. In this study, we aimed to evaluate the role of AMs during the SARS-CoV-2 infection using a co-culture of fully differentiated primary human airway epithelium (HAE) and human monocyte-derived macrophages (hMDMs). Our results confirmed abortive SARS-CoV-2 infection in hMDMs, and their inability to transfer the virus to epithelial cells. However, we demonstrated a striking delay in viral replication in the HAEs when hMDMs were added apically after the epithelial infection, but not when added before the inoculation or on the basolateral side of the culture. Moreover, SARS-CoV-2 inhibition by hMDMs seems to be driven by cell-to-cell contact and not by cytokine production. Together, our results show, for the first time, that the recruitment of macrophages may play an important role during the SARS-CoV-2 infection, limiting the virus replication and its spread.